2020 International Conference on Informatics, Multimedia, Cyber and Information System (ICIMCIS) 2020
DOI: 10.1109/icimcis51567.2020.9354313
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Hurdles to E-learning Implementation During COVID-19 Outbreak: A Case of Shaikh Zayed University

Abstract: Information and Communication Technologies (ICTs) are used extensively in various fields all over the world. E-learning has become a necessity in higher education institutions and is being deployed in educational establishments across the globe during the COVID-19 pandemic. An online survey was conducted from May to June 2020 amidst COVID-19 at Shaikh Zayed University (SZU), Khost, Afghanistan, to assess the current status and identify key challenges hurdle elearning implementation. A structural questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…[33] and [7] found that students in developing countries always encountered the problem of limited devices and the Internet. [32] have also reached similar results by reporting that a bad Internet connection is still a barrier to the acceptance of e-learning. This is one of the main reasons why the surveyed students were not satisfied with online learning and prefer face-to-face learning.…”
Section: Technical Challengessupporting
confidence: 55%
See 1 more Smart Citation
“…[33] and [7] found that students in developing countries always encountered the problem of limited devices and the Internet. [32] have also reached similar results by reporting that a bad Internet connection is still a barrier to the acceptance of e-learning. This is one of the main reasons why the surveyed students were not satisfied with online learning and prefer face-to-face learning.…”
Section: Technical Challengessupporting
confidence: 55%
“…Since the faculty is located in the country's economic capital and the majority of the students live in urban area. In our study we didn't face the problem of the interruption of power and electricity like in [33,32]. Furthermore, to ensure the satisfaction of the students, quality of e-learning must be provided [40].…”
Section: Technical Challengesmentioning
confidence: 99%
“…During the points mentioned and analyzed for the use of these different virtual platforms, the financing aspect is essential due to various factors. Both by the student entity (University or college), as well as by the students for the usability of the conference applications [21].…”
Section: Discussionmentioning
confidence: 99%
“…A review of e-learning challenges before and after the pandemic 7 Th existing literature presents similar challenges to elearning, including and not limited to financial constraints, inadequate internet bandwidth, lack of operational e-learning policies, technical e-learning skills, interest, and commitment to the teaching (Nasrat, Khamosh, & Lavangnananda, 2020). Few researchers discuss these challenges further on three levels: university management, facilitators and students.…”
Section: 2mentioning
confidence: 99%
“…With regard to facilitators/lecturers, a lack of training on the usage of technologies, difficulties in creating digital content, and poor internet connectivity are among the challenges slugging the adoption of e-learning (Nasrat, Khamosh, & Lavangnananda, 2020). As for students, they are reported facing similar challenges as those facing the instructors.…”
Section: 2mentioning
confidence: 99%